Communication challenges faced by customers who are less proficient in English and Afrikaans at two South African state-owned enterprises - Khumalo, Lungisani X.; Ditsele, Thabo; Rwodzi, Christopher (Literator, 2023)
The Use of Official Languages Act (No. 12 of 2012) applies to all national departments and state-owned enterprises (SOEs) in South Africa and stipulates that they should promote multilingualism when interacting with members of the public and/or customers. The main aim of this study was to investigate how two SOEs, that is, the South African Post Office (SAPO) and Passenger Rail Agency of South Africa (PRASA), manage communication with their customers, particularly those who cannot communicate in English and Afrikaans. Data for this study were gathered through a mixed method approach. Quantitative data (i.e., a Likert-type scale) were gathered from 120 participants who were customers of the two SOEs, and qualitative data (i.e., face-to-face interviews) were gathered from 20 interviewees who were drawn from the 120 participants. The researcher was based in Gauteng, and conducted the study in that province because it was convenient and practical. The data were gathered in Tshwane, Ekurhuleni, Johannesburg, and the West Rand. The study found that customers believed that those who could not communicate in English and Afrikaans did not receive adequate information from the SOEs because of this shortcoming. The study also revealed that the marginalisation of Black South African Languages (BSALs) by SOEs was regarded as justified by some respondents because these SOEs provided services to customers who speak different languages. The study also found that other participants felt that it was necessary for SOEs to continue to use English as the main language of communication with customers because it is an international language, which also promotes unity among the people of South Africa, including customers of SOEs.ContributionThe major contribution of this article to scientific knowledge is that it dwells deeper into how customers of the two SOEs who are less proficient in English and Afrikaans felt excluded in communication with all customers, and this is the first article to do so. Through this article, there is potential that the SOEs will appreciate that customers who are less proficient in English and Afrikaans want major adjustments to be made so they too can feel a sense of belonging and also fully appreciate what is being communicated to all customers, regardless to their proficiency in the two languages.